Outcomes after implementation of a multimodal standard care pathway for laparoscopic colorectal surgery. Issue 8 (15th May 2014) - Larson, D. W.; Lovely, J. K.; Cima, R. R.; Dozois, E. J.; Chua, H.; Wolff, B. G.; Pemberton, J. H.; Devine, R. R.; Huebner, M.
<x xml:space="preserve">Abstract</x> Background The aim of the study was to assess which aspects of an enhanced recovery programme are associated with better outcomes following laparoscopic colorectal surgery. Methods A database of laparoscopic colorectal procedures performed in 2011 was reviewed. Elements of the enhanced recovery programme and compliance were evaluated for short‐term (30‐day) outcomes. Individual elements included gabapentin, celecoxib, intrathecal analgesia, diet, postoperative fluids, and paracetamol/non‐steroidal anti‐inflammatory drug pain management. Results Five hundred and forty‐one consecutive procedures were included. Compliance with the enhanced recovery programme elements ranged from 82·4 to 99·3 per cent. Median length of hospital stay was 3 (i.q.r. 2–5) days, with 25·9 per cent of patients discharged within 48 h. Patients without complications had a median length of stay of 3 (i.q.r. 2–4) days if compliant and 3 (3–5) days if not (P < 0·001). Low oral opiate intake (oral morphine equivalent of less than 30 mg) (odds ratio (OR) 1·97, 95 per cent confidence interval 1·29 to 3·03; P = 0·002), full compliance (OR 2·36, 1·42 to 3·90; P < 0·001) and high surgeon volume (more than 100 cases per year) (OR 1·50, 1·19 to 1·89; P < 0·001) were associated with discharge within 48 h. Compliance with the elements of oral intake and fluid management in the first 48 h was associated with a reduced rate of complications (8·1 versus 19·6 per cent; P = 0·001). Median oral opiate intake was 37·5 (i.q.r. 0–105) mg in 48 h, with 26·2 per cent of patients receiving no opiates. Conclusion Compliance with an enhanced recovery pathway was associated with less opiate use, fewer complications and a shorter hospital stay.